Fresno County Bar Association Law Day Luncheon: Attorney General John Van de Kamp - Watkins, Howard::::::::: (1987)
California Legal Secretaries, Inc. President Joyce Seymour, Fresno County Fresno County Legal Secretaries' Association President Mildred Christian, San Joaquin Association of Legal Assistants (SJALA) President Lee Cabibi, Attorney General John Van de Kamp, former Justice Cruz Reynoso, Law Day Co-Chairs Sandra Snyder and Debra Kazanjian, Fresno County Bar Association President Howard Watkins and Samuel Palmer III Photo used in July-August issue of Fresno County Bar Association Bar Bulletin